THE LEGAL POSITION OF LECTURER AT UNIVERSITY WHICH INCORPORATED AS FOUNDATION IN INDONESIA - Surya Nita (Faculty of Law, Universitas Sebelas Maret, 2016)
The Foundation is Organizing Body of Universities carry out the functions and purposes of workers hired as a lecturer in providing formal educational services to students. Lecturer profession specialized field of work with the principle of upholding the professionalism of legislation, laws, codes of conduct, as well as religious values and ethics. The issue of this article as follows: (1) How does the organization of University carried out by people in Indonesia ?; (2) How does the position of lecturer in University which incorporated as foundation in Indonesia ?; (3) How is the regulation on legal position of lecturer in University which incorporated as foudation in the future?. Juridical empirical research methods in the field of law aims to completely describe the characteristics of certain situation, private or group behavior. The research use sample purposive sampling that is case of lecturer with Foundation in Industrial Court of Yogyakarta and Medan. The research use qualitative descriptive for data analysis to describe legal position of lecturer in University which incorporated as Foundation in Indonesia. Based on result, the management model of University is Private University for university management. The rights and obligation of Private University management rely on the Foundation. Autonomy,accountable, fair and transparent that are regulated on the Law Number 12 of 2012 on Higher Education can not well implemented due to the Foundation as legal body has the rights and obligation that effect any activities of University which incorporated as Foundation in Indonesia. Lecturer, as a professional, is appointed in accordance with regulation in using work relationship based on labor agreement contains the terms of employment rights and obligations of the parties with the principle of equality based on the Law Number 13 of 2003 on Employment. The use of the term mutual agreement is not known in Employment Act. In the future, in order to meet the ground of Pancasila Justice, the legal relationship between the lecturers and the foundation is a relationship based on the principles of Pancasila Justice provides legal protection to the weak position because it ensures the balance of rights and obligations of the parties.